THE TRANSCRIPTIONAL BIOMARKERS FOR AGING-RELATED DISEASES: THE MULTI-ETHNIC STUDY OF ATHEROSCLEROSIS. (11th November 2018) - Ding, J; Lohman, K; Kritchevsky, S; Molina, A; Nicklas, B; Bertoni, A; Post, W; Liu, Y
Abstract: Aging-related diseases and conditions seriously compromise the quality of life among older adults. We previously identified age-related transcriptional networks associated to fundamental aging mechanisms including autophagic flux for the top network. Our objective is to examine the utility of this network as a biomarker for aging-related diseases. We used ordinal logistic regression to investigate the cross-sectional relationship of the autophagic flux network (3 transcripts) with the comorbidity index, defined as the number of prevalent aging-related diseases, at the 2010–2012 Multi-Ethnic Study of Atherosclerosis (MESA) examination in 1, 264 community-based adults, 47% Caucasian, 32% Hispanic, 21% African American, 51% female, aged 55–94 years. The eigengene score of the autophagic network was positively associated with the comorbidity index (OR=1.16 per SD increment in the eigengene score, p=0.048), after adjusting for age, gender, ethnicity, smoking, alcohol drinking, physical activity, education, and body mass index. This association was qualitatively consistent across gender and ethnicity subgroups (p for interactions > 0.05). Two autophagic genes, MCL1 (OR=1.23, p=0.007) and TSC22D3 (1.17, 0.032), but not CEBPD (1.03, 0.71), were associated with the comorbidity. This network was positively associated with type-2 diabetes (OR=1.23, p=0.023), chronic kidney disease (1.26, 0.037), hip fracture (2.14. 0.035), and hypertension (1.19, 0.002), marginally with cancer (1.19. 0.07), but not with cardiovascular disease (0.91, 0.32), chronic obstructive pulmonary disease (1.27, 0.23), and dementia (0.93, 0.78). In conclusion, our findings suggest that the autophagic flux transcriptional network reports aging mechanisms underlying multiple aging-related diseases.